2021
DOI: 10.3389/fendo.2021.657953
|View full text |Cite
|
Sign up to set email alerts
|

Neural Cell Adhesion Molecule Regulates Osteoblastic Differentiation Through Wnt/β-Catenin and PI3K-Akt Signaling Pathways in MC3T3-E1 Cells

Abstract: Neural cell adhesion molecule (NCAM) is involved in cell multi-directional differentiation, but its role in osteoblast differentiation is still poorly understood. In the present study, we investigated whether and how NCAM regulates osteoblastic differentiation. We found that NCAM silencing inhibited osteoblast differentiation in pre-osteoblastic MC3T3-E1 cells. The function of NCAM was further confirmed in NCAM-deficient mesenchymal stem cells (MSCs), which also had a phenotype with reduced osteoblastic potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 42 publications
(55 reference statements)
2
15
0
Order By: Relevance
“…Multiple studies have shown that the expression of Wnt6, Wnt10a, and Wnt10b inhibits the differentiation of MSCs into adipocytes while promoting MSCs differentiation into osteoblasts through the canonical Wnt pathway [34]. Furthermore, lots of studies have revealed that Wnt/β-catenin plays an important role in the proliferation and differentiation of embryonic osteoblasts [35,36]. Met also activated the Wnt/βcatenin signaling pathway to reduce inflammation and apoptosis, according to Zhang et al [37].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that the expression of Wnt6, Wnt10a, and Wnt10b inhibits the differentiation of MSCs into adipocytes while promoting MSCs differentiation into osteoblasts through the canonical Wnt pathway [34]. Furthermore, lots of studies have revealed that Wnt/β-catenin plays an important role in the proliferation and differentiation of embryonic osteoblasts [35,36]. Met also activated the Wnt/βcatenin signaling pathway to reduce inflammation and apoptosis, according to Zhang et al [37].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that neural cell adhesion molecule silencing inhibits osteoblast differentiation by inactivating Wnt/β-catenin and PI3K-Akt signaling pathways. CD137 may be involved in p53 and Wnt/β-catenin signaling pathways, thereby regulating the imbalance of bone homeostasis and affecting bone mass ( 53 , 54 ). We hypothesized that adhesion molecules may be associated with an imbalance in bone homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 20, 2023. ; https://doi.org/10.1101/2023.03.20.533133 doi: bioRxiv preprint (20), and that its presence can regulate chondrocyte hypertrophy in chromogenic differentiation (18). The protein Fc fragment of IgG receptor IIIb (FCGR3B) is involved in the immune response and are known to bind to IgG, and has been detected to be more abundant in menisci with OA than in healthy menisci (21).…”
Section: Discussionmentioning
confidence: 99%